Traumatized German soldiers with moral injury – value-based cognitive-behavioral group therapy to treat war-related shame - Diekmann, Caroline; Issels, Leonie; Alliger-Horn, Christina; Rau, Heinrich; Fischer, Christian; Thiel, Thomas; Willmund, Gerd; Zimmermann, Peter (Frontiers in Psychiatry, 2023)
Introduction: During deployment, soldiers are confronted with potentially morally injurious events. In many cases, these events violate their personal values and belief systems, resulting in feelings of anger, alienation, guilt, and shame. The psychological distress caused by such transgressions is defined as moral injury. It remains unclear to date, which therapeutic interventions are most appropriate for addressing this specific psychological condition. This study examines the effectiveness of value-based cognitive-behavioral group therapy combining elements of cognitivebehavioral therapy, acceptance and commitment therapy, spiritual care, and adaptive disclosure therapy.Conclusion: This study suggests that the special therapeutic focus in cognitive-behavioral group therapy can alter shame-based maladaptive coping behaviors in response to war-related moral injury. This study provides further evidence that therapeutic approachesthrough fostering a reconciliatory, compassionate, and forgiving approach towards oneself and otherstarget the underlying mechanisms of moral injury. Therefore, value-based cognitive-behavioral interventions should be considered as a standard element of trauma care in a military setting. Future studies should further examine such interventions in randomized control trials. It would also be particularly valuable for future studies to include a follow-up time point.